Magnetic molecularly imprinted polymers synthesized by surface‐initiated reversible addition‐fragmentation chain transfer polymerization for the enrichment and determination of synthetic estrogens in aqueous solution. Issue 15 (August 2015) - Chen, Fangfang; Zhang, Jingjing; Wang, Minjun; Kong, Jie
<x xml:space="preserve">Abstract</x> J. Sep. Sci. 2015, 38, 2670–2676 DOI: 10.1002/jssc.201500407 The novel magnetic molecularly imprinted polymers for enrichment of synthetic estrogens were synthesized via surface‐initiated reversible addition addition‐fragmentation chain transfer polymerization using diethylstilbestrol as template. The uniform imprinted surface layer and the magnetic property of the magnetic molecularly imprinted polymers favored a fast binding kinetics and rapid analysis of target molecules of synthetic estrogens, i.e. diethylstilbestrol, hexestrol, dienestrol, and bisphenol A, with excellent recovery and detection limit. It provides a versatile strategy for the preparation of well‐defined solid‐phase extraction materials for the analysis and extraction of synthetic estrogens in water.